Implementasi hukum tata ruang proteksi sawah untuk Agrotourism dan UMKM di Bali - Erniasih, Ni Wayan; Prathama, Anak Agung Gede Agung Indra; Silantara, I Gede Gandhi; Sujata, I Ketut; Suryati, I Gusti Ayu Komang; Buana, I Wayan Asana Bintang (Penerbit Goodwood, 2025)
Purpose: This study aims to explore the implementation of spatial planning legal policies to protect rice fields and residential areas that are vital to supporting agritourism and the growth of MSMEs (Micro, Small, and Medium Enterprises) in Penatih Dangin Puri Village, Bali. Research Methodology: A community service approach was employed, consisting of legal socialization, participatory land use training, and advocacy directed at both village authorities and regional governments. Qualitative participatory observation and documentation techniques were used to measure awareness and stakeholder engagement. Results: The program increased community understanding of spatial planning regulations and their connection to agritourism and MSME development. Stakeholders began aligning land-use practices with environmentally friendly zoning principles. Notably, early synergy emerged between village leaders and residents in preserving rice fields as agritourism assets. Conclusions: Implementing spatial planning legal policies effectively enhances local capacity for sustainable land use and economic development. Protecting agricultural and residential zones contributes to the long-term viability of agritourism and MSMEs in Bali. Limitations: The study was localized to a single village and focused on short-term awareness-building. Broader regional engagement and long-term evaluation are required to generalize findings. Contribution:This study provides a practical model for community-based spatial planning that integrates legal frameworks with sustainable tourism and MSME growth, potentially applicable to other rural tourism areas in Indonesia.